Research handbook on entrepreneurial behavior, practice and process - Teague, Bruce T.; Gartner, William B. (Research handbooks in business and management, 2020)
"What do entrepreneurs do? In a comprehensive and detailed exploration using three perspectives -behavior, practice and process - this Research Handbook demonstrates specific methods for answering that question and provides insights into the implications of pursuing that question. The authors demonstrate a variety of methods including ethnography, autoethnography, participant observation, diaries, social media platforms and multilevel research techniques to delve into the foundations of entrepreneurial behavior. In addition to reinvigorating this long dormant area of scholarship, these chapters provide scholars with the idea that the disparate perspectives on this topic are really headed in the same direction. They also demonstrate the notion that similar tools can be utilized to answer the same type of questions emanating from these different perspectives. The contributors go on to offer insights to a wide range of scholarship on organizations. Entrepreneurship scholars, PhD students, and upper level graduate and undergraduate students who want a current overview on the theories, methods and implications of studying entrepreneurship will welcome the insights explored in this Research Handbook"--Provided by publisher.